Towards Human Development Sustainability of Developing Countries (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
Human development has long become the main concern of countries across the globe to ensure that the people enjoy long, healthy and cherished lives. Human development, among other things, is related to Foreign Direct Investment (FDI). Most developing countries are dependent on FDI to develop their economies. However, before making substantial investment, foreign investors have to consider a number of things, which have yet to be determined by the existing studies. This study attempts to examine the relationships between the variables that significantly contribute to the FDI. Six hypotheses were developed to test the interrelationships among the variables. Data from thirty-eight countries were obtained from various sources including the World Bank, Davos Economic Forum and various websites. Results of correlation analysis showed that only three hypotheses were accepted and others were rejected. Corporate Governance Index is significantly related to Global Competitiveness Index and Human Development Index. Global Competitiveness Index is significantly related to Human Development Index. The other hypotheses were not supported. The findings are beneficial to business leaders and policy makers of developing countries in developing appropriate strategies to ensure outstanding corporate governance practices.